Al lu'lu' wal marjan : himpunan hadits shahih disepakati oleh Bukhari dan Muslim - Muhammad Fuad Abdul Baqi (Bina Ilmu)
tr, Jil. 1=c.1-3; Jil. 2=c.1-2; sn,jl.1,c.4; jl.2,c.3-4/ir, jil.1,c.5/why, jld.1=c.6/tr, jil.2=c.5/en, c.6/nr,jil.1=c.7